Bioactive constituents from Manilkara obovata (Sabine & G.Don) J.H.Hemsl. Issue 22 (18th November 2021) - Akosung, Emmanuel; Kenmogne, Sidonie Beactrice; Lobe Songue, Jules; Longue Ekon, Jean Pierre; Lateef, Mehreen; Ngeufa Happi, Emmanuel; Langat, Moses Kiprotich; Tabekoueng, Georges Bellier; Toze, Flavien Aristide Alfred; Stammler, Hans-Georg; Ndjakou Lenta, Bruno; Wansi, Jean Duplex; et al.
Abstract: The phytochemical investigation of the methanolic extracts of roots, stem bark, leaves and twigs of Manilkara obovata has led to the isolation of one new friedelane triterpene, lacefriedelic acid or 3 β, 23-dihydroxy D:A-friedooleanan-28-oic acid (1 ) and one new prenylated xanthone, lacexanthone or 4, 7-dihydroxy-2, 3, 3, 9, 9-pentamethyl-2, 2-dihydrofurano[2, 3-a]pyrano[2, 3-i]xanthen-13( 9H )-one (2 ) alongside twenty-four known compounds. Compounds 1 -11 are reported here for the first time from the genus Manilkara . The structures of all compounds were determined by spectroscopic analyses and X-ray crystallography. The methanolic extracts of twigs and leaves showed anti-oxidant activity of 93.2 and 91.1%, respectively, at 100 µg/mL when measured by DPPH (2, 2-diphenyl-1-picryl-hydrazyl-hydrate), while the twig extract displayed 86.3% at 100 µg/mL against the urease inhibition assay. Some isolated compounds (1 -4, 15 and 20 ) showed significant to moderate anti-oxidant activity and urease inhibition assay. It is estimated that significantly active anti-oxidants and urease inhibitors metabolized by the plant may find future application in food industry. Graphical Abstract: